Highly Efficient Photocatalytic System Constructed from CoP/Carbon Nanotubes or Graphene for Visible‐Light‐Driven CO2 Reduction. Issue 17 (28th February 2018) - Fu, Zi‐Cheng; Xu, Rong‐Chen; Moore, Joshua T.; Liang, Fei; Nie, Xiao‐Cun; Mi, Chen; Mo, Jiang; Xu, Yong; Xu, Quan‐Qing; Yang, Zhi; Lin, Zhe‐Shuai; Fu, Wen‐Fu
Abstract: Visible‐light‐driven conversion of CO2 to CO and high‐value‐added carbon products is a promising strategy for mitigating CO2 emissions and reserving solar energy in chemical form. We report an efficient system for CO2 transformation to CO catalyzed by bare CoP, hybrid CoP/carbon nanotubes (CNTs), and CoP/reduced graphene oxide (rGO) in mixed aqueous solutions containing a Ru‐based photosensitizer, under visible‐light irradiation. The in situ prepared hybrid catalysts CoP/CNT and CoP/rGO show excellent catalytic activities in CO2 reduction to CO, with a catalytic rates of up to 39 510 and 47 330 μmol h −1  g −1 in the first 2 h of reaction, respectively; a high CO selectivity of 73.1 % for the former was achieved in parallel competing reactions in the photoreduction of CO2 and H2 O. A combination of experimental and computational studies clearly shows that strong interactions between CoP and carbon‐supported materials and partially adsorbed H2 O molecules on the catalyst surface significantly improve CO‐generating rates. Abstract : In a flash : New systems for visible‐light‐driven reduction of CO2 to CO catalyzed by hybrid CoP/CNT or CoP/rGO with a Ru‐based photosensitizer in a mixed aqueous medium were constructed. A catalytic rate of 47 330 μmol h −1  g −1 and 73.4 % CO selectivity were achieved. Strong interactions between CoP and carbonaceous materials and partially adsorbed H2 O molecules on the catalyst surface greatly improved the rates of CO generation.